INFORMASI EDUKASI COVID-19 DALAM KEGIATAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Harti Yuwarti; Yuni Retna Dewi (Jurnal Pustaka Komunikasi, 2020)
This research aims to find out the educational information of public relations PT.Unilever Indonesia and Wings Group in social responsibility activities in Indonesia in the case of covid 19. The concept used is Triple Bottom Line and Theory of Excellence in Public Relations. The paradigm in this study is Constructivist. The Research approach to research is qualitative. this type of research is qualitatively descriptive. The method used is a case study. The results of the research obtained are CSR PT. Unilever and Wings Group in addressing covid 19 in Indonesia with educational messages, APD assistance, ventilator assistance, funding assistance, logistics assistance for volunteers, and hygiene assistance and cooperation with hospitals are the company's commitment to sustainable community development, addressing issues affecting people's lives and realizing actions that are appropriate to the social situation of the surrounding community and the wider community. PT Unilever and Wings Group CSR activities in the form of Charity and Philanthropic. CSR run by PT. Unilever and Wings Group are Economic, legal, ethic, and Philanthropic Responsibilities. With CSR category: Cause Promotion, Corporate Social Marketing, Corporate.